Global health ethical challenges - Benatar, S. R.; Brock, Gillian (Cambridge University Press, 2020)
Improving and promoting global health continues to be one of the largest and most important challenges facing humanity in the 21st century. The task has become even more difficult since our first edition appeared almost a decade ago, given the accelerated destruction of the planet and the associated compounded threats to health that now present themselves. This second edition aims to showcase some of these new and escalating threats, along with illuminating some of the many other obstacles we now face in partnering globally to solve these formidable challenges. By global health we mean the health of all people globally within sustainable and healthy living (local and global) conditions. In order to achieve this ambitious goal, we need to understand, among other things, the value systems, modes of reasoning, and power structures that have driven and shaped the world over the past century. We also need to appreciate the unsustainability of many of our current consumption patterns and the driving forces that lie behind these before we can address threats to the health and lives of current and particularly future generations. The world and how we live in it have been changing dramatically over many centuries, but in the past sixty years change has been more rapid and profound than ever in the past. Many positive changes have been associated with impressive economic growth, advances in science and medicine and in social policies regarding access to health promotion. These include greater focus on a primary health care approach with more equitable access, expansion of social programmes to improve living conditions, and a welcome increasing emphasis on the rights of all individuals to be equally respected"--